Comparison of ultrasound‐guided microwave ablation and ultrasound‐guided vacuum‐assisted excision for treating breast lesions of uncertain malignant potential (B3 lesions): A retrospective study. Issue 4 (15th January 2023) - Zhang, Siqi; Yang, Jianquan; Wang, Lu; Li, Juan; He, Chuanshi; Lu, Man
Abstract: Aims: To compare the safety and therapeutic effect of ultrasound (US)‐guided microwave ablation (MWA) and US‐guided vacuum‐assisted excision (VAE) for patients with B3 lesions of the breast. Methods: Patients who underwent US‐guided MWA or US‐guided VAE at Sichuan Tumor Hospital from January 2016 to December 2021 were retrospectively analyzed. The technical success rate and residual rate of the two minimally invasive surgeries were recorded. During follow‐up, differences in symptom relief, recurrence or progression, re‐intervention, incidence of adverse events, or personal satisfaction were observed between the two groups. Results: The follow‐up time was comparable between the two groups. The technical success rate was similar between the two groups; no residue was found in the US‐guided MWA group, and the residue rate in the US‐guided VAE group was 3.4%. The symptoms of the two groups were improved after the operation. The incidence of postoperative adverse events in the US‐guided MWA group was significantly lower than that in the US‐guided VAE group. Additionally, the MWA group had a lower incidence of adverse events when the tumor diameter was >2.5 cm. Compared to the US‐guided VAE group, the US‐guided MWA group had a lower rate of tumor recurrence or progression, re‐intervention rate, and higher personal satisfaction. Conclusions: The technical success rate of US‐guided MWA for B3 lesions was comparable to that of US‐guided VAE, but US‐guided MWA had a lower incidence of adverse events and a higher degree of personal satisfaction compared with US‐guided VAE.